Electrochemical Synthesis of Core-shell ZnO/CdS Nanostructure for Photocatalytic Water Splitting Application. (March 2017) - Rokade, Avinash; Rondiya, Sachin; Date, Abhijit; Sharma, Vidhika; Prasad, Mohit; Pathan, Habib; Jadkar, Sandesh
Abstract: We have successfully synthesized ZnO NRs and ZnO/CdS core-shell structures by a facile two step chemical routes viz. electrodeposition and chemical bath deposition. Plane ZnO nanorods films were deposited by using three electrode electrodeposition on FTO glass substrates. The ZnO/CdS core-shell structures were deposited by immersing plane ZnO nanorod films into a bath containing precursor solution of CdS in chemical bath deposition. Formation of ZnO NRs and ZnO/CdS core-shell structures has been confirmed by UV-Visible absorption, Raman spectroscopy and scanning electron microscopy. The synthesized ZnO NRs and ZnO/CdS core-shell structures has been also characterized for photoelectrochemical (PEC) properties, Mott-Schottky analysis, electrochemical impedance spectroscopy (EIS) and efficiency measurements of PEC system. It has been found that the photocurrent conversion efficiency in water splitting is higher for ZnO/CdS core-shell photoanode than ZnO NRs photoanode. These results suggest that addition of CdS with ZnO NRs is beneficial in increasing the visible light absorption and to enhance the photocurrent conversion efficiency in water splitting. Thus, ZnO/CdS core-shell configuration can be a prospective candidate for efficient PEC splitting of water.